If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + -6)(x + 4) = 35 Reorder the terms: (-6 + 2x)(x + 4) = 35 Reorder the terms: (-6 + 2x)(4 + x) = 35 Multiply (-6 + 2x) * (4 + x) (-6(4 + x) + 2x * (4 + x)) = 35 ((4 * -6 + x * -6) + 2x * (4 + x)) = 35 ((-24 + -6x) + 2x * (4 + x)) = 35 (-24 + -6x + (4 * 2x + x * 2x)) = 35 (-24 + -6x + (8x + 2x2)) = 35 Combine like terms: -6x + 8x = 2x (-24 + 2x + 2x2) = 35 Solving -24 + 2x + 2x2 = 35 Solving for variable 'x'. Reorder the terms: -24 + -35 + 2x + 2x2 = 35 + -35 Combine like terms: -24 + -35 = -59 -59 + 2x + 2x2 = 35 + -35 Combine like terms: 35 + -35 = 0 -59 + 2x + 2x2 = 0 Begin completing the square. Divide all terms by 2 the coefficient of the squared term: Divide each side by '2'. -29.5 + x + x2 = 0 Move the constant term to the right: Add '29.5' to each side of the equation. -29.5 + x + 29.5 + x2 = 0 + 29.5 Reorder the terms: -29.5 + 29.5 + x + x2 = 0 + 29.5 Combine like terms: -29.5 + 29.5 = 0.0 0.0 + x + x2 = 0 + 29.5 x + x2 = 0 + 29.5 Combine like terms: 0 + 29.5 = 29.5 x + x2 = 29.5 The x term is x. Take half its coefficient (0.5). Square it (0.25) and add it to both sides. Add '0.25' to each side of the equation. + 0.25 + x2 = 29.5 + 0.25 Combine like terms: + 0.25 = 1.25 1.25 + x2 = 29.5 + 0.25 Combine like terms: 29.5 + 0.25 = 29.75 1.25 + x2 = 29.75 Factor a perfect square on the left side: (x + 0.5)(x + 0.5) = 29.75 Calculate the square root of the right side: 5.454356057 Break this problem into two subproblems by setting (x + 0.5) equal to 5.454356057 and -5.454356057.Subproblem 1
x + 0.5 = 5.454356057 Simplifying x + 0.5 = 5.454356057 Reorder the terms: 0.5 + x = 5.454356057 Solving 0.5 + x = 5.454356057 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.5' to each side of the equation. 0.5 + -0.5 + x = 5.454356057 + -0.5 Combine like terms: 0.5 + -0.5 = 0.0 0.0 + x = 5.454356057 + -0.5 x = 5.454356057 + -0.5 Combine like terms: 5.454356057 + -0.5 = 4.954356057 x = 4.954356057 Simplifying x = 4.954356057Subproblem 2
x + 0.5 = -5.454356057 Simplifying x + 0.5 = -5.454356057 Reorder the terms: 0.5 + x = -5.454356057 Solving 0.5 + x = -5.454356057 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.5' to each side of the equation. 0.5 + -0.5 + x = -5.454356057 + -0.5 Combine like terms: 0.5 + -0.5 = 0.0 0.0 + x = -5.454356057 + -0.5 x = -5.454356057 + -0.5 Combine like terms: -5.454356057 + -0.5 = -5.954356057 x = -5.954356057 Simplifying x = -5.954356057Solution
The solution to the problem is based on the solutions from the subproblems. x = {4.954356057, -5.954356057}
| 2/3×5/6×14 | | 2m=74 | | 45+6x+22=75+4x | | 4+4(4x+1)=-32+6x | | sen(t)=2(t) | | 8k=6j | | 2/5x-4/9=-6 | | 8x-8/8=-11 | | 14x-(2x-3)=51 | | 5x-2x/3= | | 2y+1=4x-5 | | 0.20=0.8x+0.2y | | 10+2x+40=180 | | sin(t)=2(t) | | c+6(8)=53 | | -63=-54t | | 23+n=12 | | 2x+36=x-4 | | 6c+3.50+5.50=51 | | 5z-7=6z-6 | | 9+1/9= | | 35x^2+47x+6=0 | | 40=80u | | sin(t^3)=2(t^3) | | (4+4i)(-4+4i)= | | -4m+8=20 | | 18=2x-4(-4x+18) | | 1r+t-8r+13t= | | 4(5z+1)-7=157 | | 3+6(1-6x)= | | (6x)3=2+8 | | 4/7x=x/7 |